SHARIAH COMPLIANCE REVIEW: CASE STUDY ON SAVING CONTRACT AND FUNDING CONTRACT ON FINANCING SHARIAH COOPERATIVE ALMUBAROK - Ali Farhan (Media Mahardhika, 2023)
This study aims to explain and assess sharia compliance in KSPS Al Mubarok. The research method used is a case study with muammalah fiqh theory analysis tools. Based on the results of the analysis, it shows that the savings contracts and financing agreements made at KSPS Al-Mubarok do not fulfill the syar'I principles in their business transactions, some things that are not syar'I include; not enter into a written contract on a savings contract, combine business contracts and social contracts, and use entrusted assets without the consent of the owner of the assets